Mothers’ Self-Control and Self-Efficacy and Childbirth Complications: A Study at an Indonesian General Hospital - Agustine Ramie; Mahdalena Mahdalena (International Journal Labs, 2023)
Childbirth complications are still a big problem in developing countries, especially in Indonesia and are one of the causes of high maternal mortality. This study aims to identify the relationship between self-control and self-efficacy as an indirect cause of maternal death with the incidence of childbirth complications. An analytical descriptive design with a cross sectional method was used. 175 mothers in their maternity phase were selected using the consecutive sampling technique. Self-control was measured using the Labour Agentry Scale (LAS), while self-efficacy was measured using the Childbirth Self-Efficacy Inventory (CBSEI) which had been tested for validity and reliability, and data on the incidence of childbirth complications were obtained from hospital medical records. Univariate, bivariate, and multivariate analysis with the help of computer software. The results showed that the variables of self-control and self-efficacy had a very significant relationship with the incidence of childbirth complications (p value 0.000, ?: 0.05). Mothers with poor self-control are at risk of developing complications of childbirth by 9,014 (CI 95%: 0.929 – 87,487) times greater than those with good self-control. Poor self-efficacy is at risk of developing childbirth complications 3,815 (CI 95%: 1,851 – 7,862) times greater than those with good self-efficacy. This study proves that self-control and self-efficacy are variables that influence the existence of labor complications. Antenatal care staff need to prepare mothers from pregnancy and childbirth to have the ability to control themselves and have good self-efficacy in undergoing the delivery process.